THE INFLUENCE OF MULTIMEDIA INTERACTIVE BY USING GUIDED INQUIRY LEARNING MODEL TO STUDENTS’ CRITICAL THINKING SKILL - khoiru nisa; pramudi yanti; rini marpaung (Universitas Lampung, 2013)
ABSTRACTCritical thinking skill is important for students to overcome their daily life problem . Result of observation of class VIII SMP Negeri 1 Pardasuka, showed that students’ critical thinking skill was still low. The purpose of this research is to find out the influence of multimedia interactive by using guided inquiry learning model to students’ critical thinking skill. The aspecs of students critical thingking observed were to identify, to give example, to make differences, to interpretation, to generallized, to give assumption. Students activities observed were to give idea, to disscuss, to present, to answer questions, to ask question. This research used pretest posttest group non- equivalent designed. The sampel were students of class VIII E and class VIII F chosen at cluster randomly. The quantitative data was obtained from N-gain, and was analyzed by t-test at realibility of 5 %. Qualitative data were the students’ activity collected during process which was analyzed in the percentage of average. Students’ questionnaire responses on using multimedia interactive with guided inquiry learning was analyzed descriptively. The N-gain analysis of students critical thinking was 0,4 in average, meaning that the use of multimedia interactive using guided inquiry learning model influenced significantly toward students’ critical thinking. In term of students activities, asking questions aspect reach the highest (54,5%).